RESPONSES OF FUEL SUBSIDY REMOVAL AS SUSTAINABLE TRANSPORT POLICY (Case Study: Workers in Jakarta) - , OCTAVIANI ARIYANTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Motorization in urban areas contributes several problems such as congestion, accidents, gas emissions, noises, and infrastructure breakage. Meanwhile, most of the developing countries cannot overcome such growth activities, as well as in Jakarta, where public transportation system and service are still inadequate. During the new leadership, Jakarta government are going to reform several policies to address the transportation issues in Jakarta, as it affects travelersâ behaviour either directly or indirectly. Vice Governor of Jakarta revealed a plan to remove fuel subsidy particularly in Jakarta area which can create sustainable transport policy that is important to maintain our environment. This study is intended to understand and investigate how fuel subsidy removal policy scenarios (25%, 50%, and 100%) in Jakarta affects travellersâ behaviour and analyse such policy to support sustainable transport by using qualitative research methodology. The investigation is conducted within interviews and questionnaires to workers in Jakarta, which includes ranking scale question for traveller response options. The result shows that 50% of the respondents are not affected with fuel subsidy removal and will only response to fuel price increasing at IDR 31.400 for gasoline price and IDR 26 300 for ADO (Auto Diesel Oil) per litre to make them consider about shifting mode. Moreover, respondent's response of such policy shows a tendency of change the travel mode choices into more efficient private vehicle. Therefore, fuel policy need to evaluate further of higher taxes as an extension step to continue fuel subsidy removal policy. Further, it might need an implementation of sustainable notion in transport planning within combination of pull and push measures policy both locally and nationally.